Pair-of-Pants Decompositions of 4-Manifolds Diffeomorphic to General Type Hypersurfaces (Journal of Mathematical Study, 2025)
In this paper, we show that a smooth 4-manifold diffeomorphic to a complexhypersurface in $\mathbb{CP}^3$ of degree $d≥5$ can be decomposed as the union of $d(d−4)^2$ copiesof 4-dimensional pair-of-pants and certain subsets of ${\rm K3}$ surfaces.